Sent betalda skatter och avgifter - När bör en revisor anmärka i revisionsberättelsen? - Nilsson Early,Hampus (2020)
Auditing can be dated back to the 13th century. Back then it was a tool for the company’s owner to gain insight into the business. The area, that is auditing, has since then evolved and the definition of a stakeholder is broader than ever. In the 1940s, Sweden legislated that the auditing process also should include a requirement to audit the company’s administration. The requirements have now evolved further as to also include the auditing of the company’s tax payments. The thesis addresses when an auditor should comment in the audit report that a company has paid their taxes too late. This is done both by studying the legislative preparatory materials, but also by a quantitative review of the case law that exists in the field. The study shows that the quantitative data that was obtained through case law can be used to draw conclusions about when the auditor should object in their audit report. Furthermore, the purpose of the law is also discussed and compared with how the disciplinary board applies the law.
Keywords: Sent betalda skatter och avgifter; revision av skatter och avgifter; skatterevision; Aktiebolagslagen 9:34; ABL 9:34; god revisionssed